"Cette fermeture du sens sur quoi, migrant, je bute": Crossing Cultures in Mohammed Dib*. Issue 3 (27th May 2017) - Hughes, Edward J.
ABSTRACT: L'Arbre à dires, part essay, part travel diary, part cultural reflection, and the novel Si Diable veut were both published by Mohammed Dib in 1998. While they both focus on the negotiation of cultural borders and the themes of exile, language, and identity, the works generate sharply different atmospheres and can be read as contrasting panels in a diptych. They reflect, moreover, their author's pursuit of writing as interrogation and struggle.